2022
DOI: 10.1186/s12951-022-01362-4
|View full text |Cite
|
Sign up to set email alerts
|

Graphene quantum dots rescue angiogenic retinopathy via blocking STAT3/Periostin/ERK signaling

Abstract: Background Pathological retinal angiogenesis resulting from a variety of ocular diseases including oxygen induced retinopathy, diabetic retinopathy and ocular vein occlusion, is one of the major reasons for vision loss, yet the therapeutic option is limited. Multiple nanoparticles have been reported to alleviate angiogenic retinopathy. However, the adverse effect cannot be ignored due to the relatively large scale. Graphene quantum dots (GQDs) have shown potential in drug delivery and have been… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…Zhao et al., reported the development of graphene quantum dots (also referred to as CDs) as biocompatible anti‐angiogenic nanomedicines that are effective in treating pathological retinal neovascularization by disrupting the STAT3/periostin/ERK pathway and subsequent downstream of cell cycle pathways by biocompatible CDs nanomaterials ( Figure a). [ 73 ] The number of capillary‐like structures decreased in the CDs treated groups in comparison to the control groups, as shown in Figure 5b,c. To further verify the anti‐angiogenic properties of CDs in vitro, Zhao et al.…”
Section: Ophthalmic Applications Of Cd‐based Nanomaterialsmentioning
confidence: 90%
See 1 more Smart Citation
“…Zhao et al., reported the development of graphene quantum dots (also referred to as CDs) as biocompatible anti‐angiogenic nanomedicines that are effective in treating pathological retinal neovascularization by disrupting the STAT3/periostin/ERK pathway and subsequent downstream of cell cycle pathways by biocompatible CDs nanomaterials ( Figure a). [ 73 ] The number of capillary‐like structures decreased in the CDs treated groups in comparison to the control groups, as shown in Figure 5b,c. To further verify the anti‐angiogenic properties of CDs in vitro, Zhao et al.…”
Section: Ophthalmic Applications Of Cd‐based Nanomaterialsmentioning
confidence: 90%
“…e,f) HUVEC sprouting was quantified by measuring the sprouting length of the HUVECs and the number of sprouts surrounding the sphere. Reproduced with permission [73]. Copyright 2022, Springer Nature.…”
mentioning
confidence: 99%
“…Zhao et al (Zhao, Gui et al, 2022) found that graphene quantum dots (average particle size of 3.6 nm) inhibited the proliferation and cell migration of human umbilical vein endothelial cells in vitro. In the oxygen-induced retinopathy (OIR) model, graphene quantum dots were effective in ameliorating pathological angiogenesis.…”
Section: Anti-angiogenesis (Angiogenesisrelated Eye Diseases)mentioning
confidence: 99%
“…14). 268 Pramanik et al reported that GQDs linked to human antimicrobial peptide (LL-37) and human neutrophil polypeptide (HNP1) inhibit viral infection by blocking the binding of the SARS-COV-2 variant (B.1.617.2) of the spike protein receptor binding domain (RBD) to angiotensin converting enzyme 2 (ACE2) in human cells. Compared with GQDs that are combined with a single peptide, the inhibition efficiency of the LL-37 and HNP1 dual-polypeptide combination was greatly improved.…”
Section: Biological Applications Of Quantum Dotsmentioning
confidence: 99%